2006
DOI: 10.1007/s10147-006-0567-4
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of concurrent cisplatin use during primary and adjuvant chemoradiation therapy: a phase I study in Japanese patients with cancer of the uterine cervix

Abstract: For Japanese patients with UCC receiving primary or adjuvant CCRT therapy, the recommended CDDP dose was determined to be 30 mg/m(2) for the weekly schedule and 75 mg/m(2) for the monthly schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Therefore, there are no feasibility data for this protocol evaluated by standard DLT criteria, as Watanabe et al 6 stated in their report. Keys et al,3 in GOG-123, showed that 90% of patients were able to receive four or more courses of cisplatin.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…Therefore, there are no feasibility data for this protocol evaluated by standard DLT criteria, as Watanabe et al 6 stated in their report. Keys et al,3 in GOG-123, showed that 90% of patients were able to receive four or more courses of cisplatin.…”
mentioning
confidence: 88%
“…However, these studies 2,3 did not describe the details or the number of patients who required treatment modification and/or treatment delay, especially in regard to cisplatin administration. As mentioned above, Watanabe et al 6 have now stated explicitly that more than a 7-day treatment delay constitutes a DLT. Can we not conclude that 8-14 days of delay in cisplatin administration is clinically acceptable in CCRT?…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…The first concerns the feasibility of using the standard chemotherapy of weekly 40 mg/m 2 cisplatin concurrently with radiotherapy. There have been several reports that Japanese cervical cancer patients frequently experienced severe toxicities, and investigators concluded that CCRT using weekly 40 mg/m 2 cisplatin may not be feasible for Japanese patients [2,3]. The second is that there are limited data on CCRT using high-dose-rate intracavitary brachytherapy (HDR-ICBT) [4,5].…”
Section: Introductionmentioning
confidence: 98%